2010
DOI: 10.1029/2009ja015035
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous occurrence features of the preliminary impulse of geomagnetic sudden commencement in the South Atlantic Anomaly region

Abstract: [1] Occurrence features of the preliminary impulse (PI) of geomagnetic sudden commencement (SC) both in the Pacific Ocean and South Atlantic Anomaly (SAA) regions were investigated using the long-term magnetic field data obtained from the Circum-pan Pacific Magnetometer Network (CPMN) and NICT Space Weather Monitoring (NSWM) magnetometer networks. The low-latitude preliminary reverse impulse (PRI) at Okinawa (OKI: dip latitude = 37.97°) in the Pacific Ocean region appeared in all the magnetic local time (MLT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 43 publications
(98 reference statements)
0
14
0
Order By: Relevance
“…The daily range of the S q ( H ) is greater at Huancayo than Tirunelveli. This is owing to the weaker background geomagnetic field at Huancayo, which leads to larger ionospheric conductivities [ Shinbori et al , ]. The S q variations derived using only days when the maximum K p is equal to or less than 2.0 yielded almost identical results.…”
Section: Resultsmentioning
confidence: 99%
“…The daily range of the S q ( H ) is greater at Huancayo than Tirunelveli. This is owing to the weaker background geomagnetic field at Huancayo, which leads to larger ionospheric conductivities [ Shinbori et al , ]. The S q variations derived using only days when the maximum K p is equal to or less than 2.0 yielded almost identical results.…”
Section: Resultsmentioning
confidence: 99%
“…Although there is a discrepancy on IMF dependence of nighttime amplitude, above description indicates that the LT variation of SC amplitude does not depend much on longitude except the South Atlantic anomaly region. However, number of SCs and SIs used in these analyses is too small, and the amplitude is averaged over several stations except Sugiura (1953) and Shinbori et al (2010). When we determine the best local time of a particular station to apply Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary analysis of geomagnetic variations has shown large variations in the Pantanal data when compared with data from six geomagnetic observatories in the same range of latitude or longitude, what was attributed to effects generated by the SAMA (Siqueira and Pinheiro 2015). However, other studies have shown that amplitude enhancement of geomagnetic variations in the SAMA is restricted to the center region of the anomaly (Trivedi et al 2005;Shinbori et al 2010), far away from the observatory site.…”
Section: Introductionmentioning
confidence: 92%
“…The Fourier coefficients obtained in the spectral analysis can be also used to derive magnetovariational transfer functions between the horizontal magnetic components of a local and a distant (reference) station. This method assumes that the magnetic field measured at a site is the sum of a normal and an anomalous field (Schmucker 1970). The normal field represents the sum of the external field and an induced field due to regional conductivity structure, whereas the anomalous field is due to local conductivity anomalies in which the normal field induces anomalous currents.…”
Section: Spectral Analysis and Discussionmentioning
confidence: 99%